AKTIVITAS FISIK BERHUBUNGAN DENGAN TINGKAT KECEMASAN PADA KOMUNITAS LANSIA DI YOGYAKARTA - Fatimatu Zahroh; Deasti Nurmaguphita; Prastiwi Puji Rahayu (Jurnal Kesehatan, 2025)
Aging is a natural life process experienced by all living beings. At this stage, older adults undergo a decline in bodily functions, including certain physical, psychological, and social aspects. Anxiety is one of the most common problems faced by older adults. Physical activity is an important factor in managing anxiety, as it can help reduce anxiety levels in the elderly. Lowering anxiety levels among older adults is expected to have a significant positive impact on their health and quality of life. This study aims to examine the relationship between physical activity and anxiety levels among the elderly community in Banguntapan, Bantul, Yogyakarta. This study employed a quantitative correlational design with a cross-sectional approach. The subjects consisted of 75 elderly members of the Babadan hamlet’s elderly community health post (Posyandu Lansia) in Banguntapan, Bantul, Yogyakarta Special Province, selected using a total sampling technique. The results showed that 25 respondents (64.1%) reported moderate levels of physical activity, while 26 respondents (66%) experienced mild anxiety levels. The Spearman’s Rank test indicated a significance value of 0.000 (<0.05). Therefore, it can be concluded that there is a significant relationship between physical activity and anxiety levels among the elderly community in Banguntapan, Bantul, Yogyakarta Special Province.